2017
DOI: 10.1136/bmjopen-2017-016438
|View full text |Cite
|
Sign up to set email alerts
|

Validation of two case definitions to identify pressure ulcers using hospital administrative data

Abstract: ObjectivePressure ulcer development is a quality of care indicator, as pressure ulcers are potentially preventable. Yet pressure ulcer is a leading cause of morbidity, discomfort and additional healthcare costs for inpatients. Methods are lacking for accurate surveillance of pressure ulcer in hospitals to track occurrences and evaluate care improvement strategies. The main study aim was to validate hospital discharge abstract database (DAD) in recording pressure ulcers against nursing consult reports, and to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
10
2
Order By: Relevance
“…We used the structured fields from the nursing documentation section of the EHR to record HAPrIs. We chose to use the structured fields from nursing documentation because a prior study showed that International Classification of Diseases codes underreport HAPrIs [ 21 ], likely because HAPrIs are noticed by nurses during head-to-toe skin assessments but not always flagged for inclusion in physician notes or billing codes. Furthermore, we relied on nursing documentation because it is the only accurate source of data for the date and time the HAPrI developed.…”
Section: Methodsmentioning
confidence: 99%
“…We used the structured fields from the nursing documentation section of the EHR to record HAPrIs. We chose to use the structured fields from nursing documentation because a prior study showed that International Classification of Diseases codes underreport HAPrIs [ 21 ], likely because HAPrIs are noticed by nurses during head-to-toe skin assessments but not always flagged for inclusion in physician notes or billing codes. Furthermore, we relied on nursing documentation because it is the only accurate source of data for the date and time the HAPrI developed.…”
Section: Methodsmentioning
confidence: 99%
“…Although, cross-sectional surveys by the ANQ showed similar but even lower prevalence rates (1.8%) compared to our study data (1.92%). It has been reported that administrative data do not provide valid data for this NSO due to several reasons [48][49][50]. This fact seems to…”
Section: Discussionmentioning
confidence: 96%
“…The described efforts to “improve the accuracy of clinical documentation” are consistent with other studies conducted in Australia ( 25 ) and specifically on PI ( 1 , 2 ). Studies conducted in Canada ( 29 , 30 , 36 ), Portugal ( 37 ), UK ( 38 ), and USA ( 39 ) also highlighted the need for quality improvement processes for PI clinical documentation. Nursing documentation improvement is a vital component of the complex capacity building programs on PI prevention in acute care services and is relied on by coders ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%